Formal neurocognitive function and anti-N-methyl-D-aspartate receptor antibodies in paediatric lupus - Gary Gilkeson; Bethany Wolf; Tamara K Nowling; Mary Kral; Natasha McKerran Ruth (Lupus Science and Medicine)
Objective SLE is a chronic multisystem autoimmune inflammatory disease impacting a number of organs, including the central nervous system (CNS). The pathophysiology of CNS lupus is multifactorial, making diagnosis problematic. Neurocognitive (NC) testing and specific biomarkers to identify the development of neuropsychiatric (NP) symptoms in lupus are needed. Paediatric patients with SLE have high incidence of NP disease . While serum anti-N-methyl-D-aspartate receptor (NMDAR) antibodies have shown promise as a biomarker of NP in adults with SLE, much less is known with regard to paediatric patients with SLE.Methods We performed a cross-sectional study in paediatric patients with SLE. Serum NMDAR antibodies were measured and compared with levels in patients with juvenile idiopathic arthritis (JIA). Formal NC testing was performed in accordance with the Childhood Arthritis & Rheumatology Research Alliance neuropsychological core test battery. NC functioning was compared in the two groups and with NMDAR antibody levels.Results Serum NMDAR antibody levels were significantly higher in paediatric patients with SLE compared with patients with JIA. There were no significant correlations between NMDAR antibody levels and any measure of NC functioning. In an exploratory examination of anti-ribosomal P (RibP) antibody and NC functioning in a subset of patients with SLE, RibP antibody-positive patients exhibited worse scores for Verbal Memory Index and Design Fluency Test Switching compared with RibP antibody-negative patients. A globally significant association between disease status and NC functioning was observed. Specifically, patients with SLE had lower scores compared with patients with JIA for full-scale IQ, letter–word recognition, reading fluency and calculation skills after adjusting for multiple comparisons.Conclusion These collective results suggest that although serum NMDAR may serve as a biomarker, formal NC testing is superior in identifying paediatric patients with SLE with NP manifestations. RibP also may potentially serve as a biomarker of NP manifestations in paediatric patients with SLE. Additional and longitudinal studies are needed.